Prevalence and clinical profile of hepatitis C virus infections in multitransfused thalassemic patients in the capital twin cities of Pakistan - Z. Z. Piracha; U. Saeed; R. Uppal; M. R. Uppal; A. Ahmad Khan; M. Abdullah; K. Mari; A. Basra; S. S. Gilani; M. N. Tariq; D. U. Ozsahin; B. Uzun; et al. (Brazilian Journal of Biology)
Abstract Hepatitis C virus (HCV) presents a significant global health concern, affecting 3.3% of the world's population. The primary mode of HCV transmission is through blood and blood products. Patients with beta thalassemia, who rely on lifelong blood transfusions, are particularly vulnerable to HCV infections. This study aimed to assess the prevalence of hepatitis C virus infections among multitransfused thalassemic patients in the twin cities of Pakistan's capital. The clinical research, involving the enrollment of 262 multitransfused beta thalassemic patients residing in the capital twin cities of Pakistan. The investigation encompassed the evaluation of hepatitis C virus presence, alanine aminotransferase (ALT) levels, serum creatinine, hepatomegaly, splenomegaly, and the occurrence of splenectomy. The overall prevalence of Hepatitis C virus infections was notably high at 55.73%. This was particularly pronounced among patients aged 20 years and older, with a 100% infection rate. In HCV-positive thalassemic patients, the average ALT level was observed to be 98 U/L, while average creatinine values stood at 0.39 mg/dL. Additionally, hepatomegaly was prevalent in 82.20% of HCV-positive thalassemic patients, featuring an average liver size increase of 4.33 cm. Splenomegaly was evident in 67.12% of HCV-positive thalassemic patients, with an average spleen size augmentation of 4.46 cm. Splenectomy was identified in 15.75% of cases. The incidence of HCV infections in the thalassemic population of Pakistan is alarmingly high. Furthermore, the risk of contracting HCV infections escalates with the advancing age of thalassemic patients. Elevated ALT levels and hepatomegaly were pervasive among the majority of HCV-positive thalassemic patients. Consequently, there is a compelling need for rigorous screening of blood products prior to transfusion to mitigate the future burden of HCV in Pakistan.